Sosialisasi Penggunaan Pegadaian Digital di Desa Jayamulya, Kecamatan Cibuaya, Kabupaten Karawang - Anita, Widya Febryari; Amruloh, Dedeng Abdul Gani; Wahidin, Wahidin; Wirman, Wirman (Jurnal ETAM, 2024)
Until now, pawnshop institutions have not played an optimal role in reducing the practices of loan sharks, debt bondage, and illegal banking. It is based on the fact that these practices are currently still occurring and are even becoming more common. It has an impact on reducing people's welfare in real terms. For this reason, it is necessary to carry out public education activities to access financial institutions, including pawnshops. The effort is carried out by socializing the use of Pegadaian Digital Service, a form of innovation PT. Pegadaian (Persero) produce. Socialization methods use formal socialization and direct socialization. The results of this community service activity provided various benefits felt by the Jayamulya Village Government, Cibuaya District, Karawang Regency, PT. Pegadaian (Persero), and the local community.